2012
DOI: 10.1080/16506073.2012.689323
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Treatment of Pathological Gambling with a Three-Year Follow-Up

Abstract: Effective therapies for pathological gambling exist, but their use is limited to about 10% of the target population. In an attempt to lower the barriers for help, Internet-based cognitive behavioural therapy (ICBT) has been shown to be effective when delivered to anon-depressed sample with pathological gambling. This study sought to extend this finding to a larger, more representative population, and also test a model to predict responder status. Following advertisement, a total of 284 participants started an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 46 publications
4
81
0
Order By: Relevance
“…eHealth services have been developed for the treatment of a variety of mental health problems [9][10][11][12][13][14][15][16][17][18][19][20] as well as for the purposes of mental health promotion and education [21][22][23]. One of the first eHealth applications applied in mental health care was OC-Check, which was developed in 1987 to assist OCD patients in larger reduction of OCD symptoms by reminding instructions and tracking intensity of the obsessions [10].…”
Section: Ehealth In Mental Health Carementioning
confidence: 99%
“…eHealth services have been developed for the treatment of a variety of mental health problems [9][10][11][12][13][14][15][16][17][18][19][20] as well as for the purposes of mental health promotion and education [21][22][23]. One of the first eHealth applications applied in mental health care was OC-Check, which was developed in 1987 to assist OCD patients in larger reduction of OCD symptoms by reminding instructions and tracking intensity of the obsessions [10].…”
Section: Ehealth In Mental Health Carementioning
confidence: 99%
“…In addition to problem gambling improvement (based on problem gambling scores),these studies also found improvements in gambling behaviours, anxiety, and depression [9]. Significant improvements in problem gambling, gambling frequency [8] [11], faulty cognitions surrounding gambling [19], alcohol consumption, [11] and distress [19] [23] were also noted in pre-post intervention studies that did not include a control group. ,.…”
Section: Principle Findingsmentioning
confidence: 99%
“…Specific gambling related harms scales included the Problem Gambling Severity Index (PGSI) [6] [12] [22] [16] [23], Gambling Attitudes Scale (GAS) [7], South Oakes Gambling Screen (SOGS) [20], SOGS-R [19], and SOGS-RA [7], National Opinion Research Center DSM Screen for Gambling Problems (NODS) [8] [9] [11], Problem Gambling Significant Other Impact Scale (PG-SOIS) [13] and the Diagnostic and Statistical Manual for Mental Disorders criteria for pathological gambling (DSM IV) [6]. Of these scales the PGSI and the NODS were the most popular.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations